Singkil dalam Lintasan Sejarah: Identitas Wilayah dan Asal Usul Etnisnya - A. Aslym Combih (Dampeng: Journal of Art, Heritage and Culture, 2025)
This study aims to trace the origins of the ethnic groups and the various designations of the indigenous peoples inhabiting the Aceh Singkil and Subulussalam regions, as well as to examine the historical processes of migration and assimilation that have shaped their cultural identity. Employing historical research methods, the study follows the stages of heuristics, source verification, interpretation, and historiography. The findings reveal that the name "Singkil" has been known since the 15th century, with various spellings recorded by historical figures such as Tom Pires, Petrus Plancius, and Sheikh Abdur Rauf as-Singkily. To this day, diverse terms are used to refer to the indigenous ethnic group and their language, including Singkil Tribe, Julu Tribe, Orang Hulu, Pakpak Boang, and Kade-kade Language. Historical and anthropological evidence suggests significant physical and cultural similarities between the Singkil people and other ethnic groups such as Batak, Karo, Gayo, Alas, Kluet, and Pakpak, all of whom are believed to share a common ancestry rooted in prehistoric Austro-Melanesoid migrants. Furthermore, centuries of interaction and intermarriage with other ethnic groups—including the Minangkabau, Nias, Acehnese, Indians, and Arabs—have enriched the cultural identity of the Singkil people. Islamic cultural influences, introduced by figures such as Sheikh Abdur Rauf and Hamzah Fansuri, are also believed to have originated from Arab lineages.  Abstrak: Penelitian ini bertujuan untuk menelusuri asal-usul etnis dan penamaan suku asli yang mendiami wilayah Kabupaten Aceh Singkil dan Subulussalam, serta menelusuri proses sejarah migrasi dan asimilasi yang membentuk identitas kultural masyarakat setempat. Dengan menggunakan metode penelitian sejarah, penelitian ini melalui tahapan heuristik, verifikasi sumber, interpretasi, dan historiografi. Hasil penelitian menunjukkan bahwa nama “Singkil” telah dikenal sejak abad ke-15, dengan berbagai varian penulisan oleh tokoh-tokoh sejarah seperti Tom Pires, Petrus Plancius, dan Syeikh Abdur Rauf as-Singkily. Nama dan identitas etnis masyarakat asli Singkil hingga kini masih menunjukkan keberagaman penyebutan, seperti Suku Singkil, Suku Julu, Orang Hulu, Pakpak Boang, hingga Bahasa Kade-kade. Temuan historis dan antropologis menunjukkan adanya kesamaan fisik dan budaya antara suku Singkil dengan etnis Batak, Karo, Gayo, Alas, Kluet, dan Pakpak, yang diduga berasal dari satu rumpun manusia purba Austro-Melanesoid yang bermigrasi sejak masa prasejarah. Selain itu, proses percampuran budaya dengan pendatang seperti Minangkabau, Nias, Aceh, Arab, dan India telah memperkaya identitas kultural masyarakat Singkil, termasuk dalam hal penyebaran Islam oleh tokoh-tokoh seperti Syeikh Abdur Rauf dan Hamzah Fansuri. Kata kunci: Singkil, migrasi Austro-Melanesoid, etnis Batak, sejarah lokal